Schaum's Probability & Statistics Supplementary Problem 8.64/8.65 Video Solution - Downing, Craig G. (McGraw-Hill's AccessEngineering., 2011)
This video shows how to determine the equation of a line for a set of data using the Least-Squares method. Additionally, Microsoft Excel instruction is provided.